Field Guide to Owls of California and the West. - Peeters, Hans J. (California Natural History Guides., 2007)
Most owls are almost perfectly adapted to life in the dark. Their vaguely humanoid faces reflect the spectacular evolution of their hearing and vision, which has made flight, romance, and predation possible in the near absence of light. This accessible guide, full of intriguing anecdotes, covers all 19 species of owls occurring in North America. More than an identification guide, Field Guide to Owls of California and the West describes the biology and behavior of owls to make finding and identifying them easier and watching them more enjoyable. The guide also explores the conservation challeng.